"Hoping for Greatness": Exploring the Notion of "Novicity" in Communication Support Partnerships. (December 2014) - Woodfield, Casey; Jung, Eunyoung; Ashby, Christine
This research explores the stage of novicity in communicative partnerships between new facilitators and the individuals with disabilities who use supported typing as their primary method of communication with whom they work. We interviewed novice and experienced facilitators, and typers who have recently worked with new facilitators to examine not only the series of processes through which novice facilitators experience and learn to support typing but also typers' responses to those experiences. We draw connections to sign language interpreters and paraprofessionals to highlight the complexity of providing communication access and support. Two key tracks of talk emerged—one centered on skills and the other on relationships—which we lay out in a discussion of typers' and facilitators' perspectives on expectations, training, trust, and agency. Our results suggest the critical nature of establishing individualized expectations for and by both typers and facilitators, as well as the importance of working through the distinctive experiences brought forth in this period of novicity, as fundamental elements of developing communication partnerships.